Making a Mobile Application for Information on Islamic Banking Loans Oengan Java 2 Micro Edition - Angga Kusuma Bayu Aji (Institute of Computer Science (IOCS), 2022)
Everyone who wants to borrow money either for business capital or for personal needs will definitely borrow from the bank. Borrowing money from public banks is commonplace, but borrowing money from Islamic banks is only used by some people who know about Islamic banks. The difference from borrowing money from a commercial or Islamic bank lies in the specified usury. To make it easier for customers to find out what sharia loans are like, they can use cellphones (HP). That's why this sharia loan information application via mobile phone was made. For the design process, the JWTK application software will be used and the KToolbar will be used. The design of handheld devices software is designed based on the displays needed. The display consists of menus that will make it easier for users to search for sharia loan information. It's very easy to use, just choose what type of loan you want. After that, enter the input in the form of a number and then by pressing the Wrung button, the output will automatically display the calculation results from the input. J2ME (Java 2 Micro Edition) technology is used because this technology is platform- and device-free. In addition, the memory used is very small, so it doesn't take up too much memory on existing cellphones and the installation process is so easy.